Mechanical properties of WC/Co-CNT HVOF sprayed coatings. (1st November 2020) - Staia, M. H.; Mejias, A.; La Barbera, J. G.; Puchi-Cabrera, E.S.; Villalobos-Gutierrez, C.; Santana, Y. Y.; Montagne, A.; Iost, A.; Rodriguez, M. A.
ABSTRACT: Coatings based on WC–12Co, with and without the reinforcement of carbon nanotubes (CNTs) have been deposited by means of the HVOF thermal spraying technique on a SAE 1020 steel substrate. The aim of the present study is to evaluate in detail the influence of the 36 h milling time on both feedstock powders, particularly on the mechanical properties of WC-12Co coatings, with (WCCNT ) and without (WCCONV ) CNTs addition. Properties such as hardness, apparent yield stress and fracture toughness were observed to exhibit an improvement due to CNTs addition, whereas the elastic modulus was found to be insensitive to the CNTs content. These findings could explain the enhancement of the wear resistance of the CNTs-reinforced coatings (WCCNT ) reported in the literature.